Researching factors and coping strategies of EFL students’ speaking anxiety - Diana, Meutia; Renandya, Willy Ardian; Dahliana, Syarifah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
English students often face challenges with speaking anxiety when asked to speak in front of the class. Many students are unaware of the factors contributing to their anxiety and lack strategies to manage it effectively. This research aims to identify the causes of speaking anxiety and the strategies EFL students use to cope with it. A descriptive qualitative approach was used, employing semi-structured interviews to gather data. Convenience sampling was applied to select six English students who had completed a speaking class as participants. The findings revealed five key factors contributing to speaking anxiety: (1) lack of preparation, (2) fear of making mistakes, (3) limited English skills, (4) excessive worry about meeting academic targets, and (5) fear of others’ reactions. Additionally, four strategies for managing speaking anxiety were identified: (1) changing mindset, (2) relaxation, (3) building confidence, and (4) improving speaking skills.